Microsoft Excel 2019 - McGuckin, Cindy ([Packt Publishing], 2019)
"This 7-hour Microsoft Excel 2019 course is perfect for those brand new to Excel and who are using Excel 2019 or Excel 365 editions. In this course, your expert author gives you a solid grounding in the basics of Excel and guides you towards becoming more confident with spreadsheets."--Resource description page